Gut microbiota in adolescents and the association with fatty liver: the EPOCH study. (August 2018) - Stanislawski, Maggie; Lozupone, Catherine; Wagner, Brandie; Eggesbø, Merete; Sontag, Marci; Nusbacher, Nichole; Martinez, Mercedes; Dabelea, Dana
Abstract Background Recent evidence supports that the gut microbiota may be involved in the pathophysiology of non-alcoholic fatty liver disease (NAFLD), and may also offer avenues for treatment or prevention. Methods We investigated the associations among gut microbiota, diet, and hepatic fat fraction (HFF) in 107 adolescents. Magnetic resonance imaging (MRI) was used to assess HFF, and 16S rRNA gene sequencing was performed on collected fecal samples. Dietary intake was assessed using Food Frequency Questionnaires. We examined the association between gut microbiota alpha diversity and HFF, and assessed the predictive accuracy for HFF of (1) taxonomic composition, (2) dietary intake, (3) demographic and comorbid conditions, and (4) the combination of these. Results Lower alpha diversity was associated with higher HFF (β =−0.19, 95% confidence interval (CI) −0.36, −0.02). The selected taxa explained 17.7% (95% CI: 16.0–19.4%) of the variation in HFF. The combination of two of these taxa, Bilophila andParaprevotella, with dietary intake of monounsaturated fatty acids and BMIz -scores explained 32.0% (95% CI: 30.3–33.6%) of the variation in HFF. Conclusion The gut microbiota is associated with HFF in adolescents and may be useful to help identify youth who would be amenable to gut microbiota-based interventions.